Identifikasi Jebakan Kelompok Miskin Transien di Sumurarum Magelang - Yuni Indarti; Drajat Tri Kartono; Haryani Saptaningtyas (Universitas Hamzanwadi, 2025)
The issue of extreme poverty has become a global strategic issue, but ironically, transient poor households are often neglected in poverty alleviation policy schemes. This group, despite their motivation to escape poverty, is highly vulnerable to falling back below the poverty line when shocks occur. This study aims to (1) describe the conditions of transient poor households in Sumurarum Village, Magelang Regency, and (2) identify the causes of transient poverty through a participatory approach. This study uses a qualitative approach with Participatory Action Research (PAR). Data were collected through field observations, in-depth interviews, and Focus Group Discussions involving transient poor households and village officials. Data analysis was conducted qualitatively through reduction, data presentation, and conclusion drawing. The results of the study show that: 1) Transient poor households in Sumurarum Village are in a vulnerability trap, with the following characteristics: a) Marginal welfare, where households are above the poverty line but depend on fluctuating daily wages and have minimal physical assets. b) High vulnerability, where they are exposed to shocks (health, social, program failure) without adequate protection, even more vulnerable than the extremely poor who still receive social assistance. c) Systemic powerlessness, characterized by a lack of access and voice due to the failure of data collection systems and unfair access to programs at the village level. 2) Issues causing transient poverty include: a) Limited human resources (low education and informal employment), b) Inappropriate intervention design (social assistance that only provides a sense of security, not improved welfare), and c) Village institutional inefficiency (information asymmetry and lack of specific empowerment programs).